(untitled) (Research, Society and Development, 2020)
The study aimed to report the experience of a nursing student about the period of experience in adult emergency care in a city in the central region of Rio Grande do Sul. This is a descriptive study, of the type of experience, arising from the insertion of an academic from the fifth semester of the Nursing Course, from the Federal University of Santa Maria (UFSM), in activities of curricular experiences in an adult emergency service. The experience took place from December 2019 to February 2020, through the Complementary Nursing Training Program (PROFCEN). It was possible to improve techniques, learn about the role of nurses in this service, observe the working conditions that professionals face and how proper management becomes an ally to achieve quality care. It was also noticed the great demand of patients looking for care that often overcrowd the environment and cause work overload for the team of professionals. Participation in PROFCEN was extremely important for the complementarity of academic training, which allowed, in addition to knowing the role of nurse leader who works in an emergency care, to acquire experiences that improve practical skills. These enable and prepare the academic to deal with the potential, weaknesses and challenges of the service in the future.